Risk assessments questions and answers a practical approach - Perry, Pat, 1954- (Thomas Telford, 2003)
Risk assessment in the work place is obligatory, but many individuals are unsure what is suitable and sufficient. Pat Perry explains the law as it stands, what counts as best practice and how HSE guidance should be interpreted when assessing risk.